EFFECTIVE APPROACHES OF REMOTE CONTROL AND ASSESSMENT OF STUDENTS LEARNING ACHIEVEMENTS - Issabaeva, Д.Н; Issabaeva, С.Н; Rakhimzhanova, Л.Б (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
The article presents methods of control and assessment of knowledge in the context of distance learning. The definition of the term "Quality control" is given. The forms of control and assessment of knowledge are given: input, current, intermediate, final, using in the conditions of distance learning in Abai KazNPU. To study each topic of the training module, it is necessary to establish didactic goals, expressed at a certain level of knowledge assimilation. In the case of distance learning, in addition to testing the student's ability to memorize and understand the material, it is necessary to analyze problem situations, synthesize solutions, and check the compatibility of theoretical material with one's own experience. In this regard, and based on the experience of methods of control and assessment of knowledge in distance learning in a number of other countries, the methods of Open-book Exam or Open paper Exam, Open paper Exam, Open book Exam, Thinking exam are classified and recommended.